Zahlentheorie (insbesondere algebraische Zahlentheorie): 6. bis 11. Sept. 1964 - Hasse, Helmut; Roquette, Peter (Tagungsbericht, 1964)
S. Becken, Hamburg; H. Behr, Göttingen; H. Benz, Hamburg; R. Berger, Berlin; L. Bernstein, Tel - Aviv; H. Bremer, Basel; H. Brückner, Hamburg; J. W. S. Cassels, Cambridge; F. Châtelet, Besançon; M. Deuring, Göttingen; A. Dress, Kiel; M. Eichler, Basel; A. Fröhlich, London; W. D. Geyer; Tübingen; W. Habicht, Basel; G. Harder, Hamburg; H. Jacobinski, Vendelsö; W. Jehne, Heidelberg; M. Knebusch, Hamburg; M. Kneser, Göttingen; H. Koch, Berlin; I. A. Kostrikin, Moskau; T. Kubota, Türingen; E. Kunz, Heidelberg; K. Lakkis, Hamburg; W. Leopoldt, Tübigen; F. Lorenz, Tübingen; M. L. Madan, Tübingen; E. Maus, Hamburg; A. Menalda, Leiden; C. Meyer, Hamburg; A. Néron, St. Ouen; J. J. Payan, Grenoble; A. Pfister, Göttingen; H. Popp, Tübingen; G. J. Rieger, München; I. R. Schafarewitsch, Moskau; H. Zassenhaus, Columbus; H. G. Zimmer, Tübingen; H. Hasse, Hamburg; P. Roquette, Tübingen